Peripheral vascular emergencies-clinicopathological co- relation with outcome in a tertiary care centre - Jain, Ankita; Jadhav, Uday; Kulkarni, Dwarkanath; Aironi, Balaji; Potwar, Sushrut; Patil, Prashant (International Surgery Journal, 2023)
Background: Peripheral arterial disease represents a major caseload in emergency department and also is major cause of distress and socio-economic burden to patient and his/her family due to risk of complications. It has a multifactorial etilogy and requires prompt treatment to salvage the limb and prevent complications. This study is a clinic-pathological correlation between various factors and surgical outcome. Methods: It is a prospective study involving 75 patients who had presented with peripheral vascular disease with different mode of presentations. All patients underwent surgical procedure and were given inj. heparin and tab. Aspirin in post operative period. Their surgical outcome was studied and co-related with etiological factors and clinical presentation. Result: Time from onset till presentation was one of the most important factors in deciding outcome. COVID-19 also emerged as one of the important risk factors in 12 cases. Patients who had been given prior anticoagulation therapy had better outcomes. Conclusions: Outcome in peripheral vascular disease patient depends on variable factors, however starting patients prior on anticoagulants has shown more possibility of salvaging the limb.